2013
DOI: 10.1016/j.jvs.2012.08.068
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of failed endografts inserted for superficial femoral artery occlusive disease

Abstract: Failure of endografts is not associated with a deterioration in clinical state and is related to a low amputation rate. The hypothesis that covered stents do not affect options for secondary reconstructions could not be confirmed, as 25% of patients with a failure underwent a below-knee bypass. Secondary surgical bypasses are correlated with poor patency. The amputation rate after failure is low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…Previously, we have shown that overstenting of collaterals does not deteriorate clinical outcome in case of failure, suggesting that the clinical relevance of overstenting collaterals in the SFA is low. 10 In our study, only nine treated SFAs had a permanent failure, of which six were eventually treated with a surgical bypass, whereas the amputation rate was 0%, confirming the safety of the technique. To date, surgery is still considered the "gold standard" for extensive SFA occlusive disease in various guidelines that could be considered outdated.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Previously, we have shown that overstenting of collaterals does not deteriorate clinical outcome in case of failure, suggesting that the clinical relevance of overstenting collaterals in the SFA is low. 10 In our study, only nine treated SFAs had a permanent failure, of which six were eventually treated with a surgical bypass, whereas the amputation rate was 0%, confirming the safety of the technique. To date, surgery is still considered the "gold standard" for extensive SFA occlusive disease in various guidelines that could be considered outdated.…”
Section: Discussionsupporting
confidence: 73%
“…8 Patients of this cohort may also have been included in other subanalyses. 3,[9][10][11][12] Data were retrospectively collected and anonymously analyzed. Retrospective research of patients' charts is not in the scope of the Dutch Law on research with human participants, and therefore neither formal approval of the Central Committee on Research Involving Human Subjects nor patient consent was required.…”
Section: Methodsmentioning
confidence: 99%
“…18 Previously, however, we have shown that failure of these covered stents, even when extended into the PA, is not related to a clinical catastrophe. 7 In a series of 49 patients presenting with a failed covered stent, the majority had a similar or even improved Rutherford category compared to before placement. Only 20% had a deteriorated category, and the amputation rate was only 4.1% (n ¼ 2).…”
Section: Discussionmentioning
confidence: 98%
“…The concern is that a loss of collateral circulation might reduce limb salvage rate in case of an acute occlusion and may negatively affect the level of an eventual amputation, although a previous study showed no validation for this concern. 7 This emphasizes the clinical significance of knowledge of lower extremity collateral circulation.…”
Section: Introductionmentioning
confidence: 98%
“…So far this has not been studied in the aorto-iliac artery, but a previous study in the femoral artery showed not such an effect. 26 The inferior mesenteric artery is regularly overstented in EVAR cases and as such it seems reasonable to assume that this is the same in case of occlusive disease. The state of the superior mesenteric artery and celiac trunk, however, should always be assessed.…”
Section: Discussionmentioning
confidence: 99%